(untitled) (Research, Society and Development, 2020)
The need for food adaptations is growing nowadays and veganism and / or vegetarianism is one of those lifestyles, which consists of not consuming products of animal origin, be it total or partial. The industries seek to associate themselves with this market competitiveness aiming at the development of new products. This work aimed to produce a hamburger with jackfruit fiber (Artocarpus heterophyllus), plus yam (Dioscorea spp. L.) and silver green banana flour (Musa sp.), Which was developed at the Gastronomy Laboratory of the Integrated Faculties of the North of Mines for conducting physical-chemical analyzes (Moisture, Ashes, Proteins), Microbiological (Aerobic Mesophiles, Total Coliform and Thermotolerant) and Sensory Analysis. Through the analyzes it was observed that the moisture content was (3.61%), that of ash (1.18%), that of proteins (1.50%). In the microbiological analyzes it was found that there was no presence of any type of aerobic Mesophilic, Total Coliform and Thermotolerant microorganisms, indicating good hygienic-sanitary condition. In the sensory analysis, the appearance attribute showed the highest level of acceptance, indicating that (70%) of the people liked the product’s appearance extremely much. As for the flavor and color attribute, the results were (62.5%) and (67.5%) respectively, indicating that they liked the product extremely much. In the purchase intention test, it was observed that (50%) of the participants would certainly buy the product, and only (2.5%) would probably not buy it. It is concluded that the use of jackfruit fiber, yam and banana flour, is feasible to add chemical and nutritional values ​​to the hamburger, which even presenting a low protein content does not limit its production and demonstrates a great possibility of commercialization.